BIMBINGAN TEKNIS FARMAKOVIGILANS DALAM PELAPORAN EFEK SAMPING OBAT KEPADA TENAGA KESEHATAN DI FASILITAS PELAYANAN KESEHATAN DI SULAWESI UTARA - Yanita Ika Widyasari; Wibisoro Isworo; Yosica Tandilolo; Natalia A Pasalli (Jurnal Abdi Masyarakat Kita, 2026)
Reporting adverse drug reactions is an important part of pharmacovigilance, involving healthcare workers in reporting adverse drug events to detect any adverse reactions in drug use. Reporting of adverse drug reactions by healthcare workers in Indonesia is still relatively low, so technical guidance is needed for healthcare workers in healthcare facilities to improve their knowledge and awareness in reporting adverse drug reactions. The activity was attended by 45 healthcare workers from community health centers and hospitals in the North Sulawesi region. The implementation was carried out in a hybrid manner, with face-to-face meetings and online via the Zoom meeting platform. Materials covered the importance of pharmacovigilance and understanding of adverse drug reactions (KTD/ESO) for healthcare workers, the application of pharmacovigilance in reporting adverse drug reactions in healthcare facilities, and the practice of inputting adverse drug reactions into the e-meso application. The average pretest score of participants was 74.4, reflecting a fairly good level of initial understanding. After receiving the educational materials, the average posttest score increased to 95.6, indicating a significant increase in participants' understanding of pharmacovigilance material. The average score difference (gain) reached 21.1 points, indicating a positive impact of this activity on increasing participants' knowledge. A further impact of this activity was an increase in the number of reports of drug side effects from healthcare workers who participated in the technical guidance.